2011
DOI: 10.1186/1477-7525-9-74
|View full text |Cite
|
Sign up to set email alerts
|

Towards a brief definition of burnout syndrome by subtypes: Development of the "Burnout Clinical Subtypes Questionnaire" (BCSQ-12)

Abstract: BackgroundBurnout has traditionally been described by means of the dimensions of exhaustion, cynicism and lack of eficacy from the "Maslach Burnout Inventory-General Survey" (MBI-GS). The "Burnout Clinical Subtype Questionnaire" (BCSQ-12), comprising the dimensions of overload, lack of development and neglect, is proposed as a brief means of identifying the different ways this disorder is manifested. The aim of the study is to test the construct and criterial validity of the BCSQ-12.MethodA cross-sectional des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 41 publications
5
83
0
2
Order By: Relevance
“…Furthermore, the fact that the study population consisted of employees of a single university, who were ultimately self-selected, and the difference found in the response rates by type of occupation, reduced the possibilities for generalising our results. We also observed that grant holders were more participative than others and were therefore over-represented, which can be explained by their reduced tendency to show neglect [13]. In general, as we did not have sociodemographic data from the total reference population, it was not possible to contrast to what extent the obtained sample was representative of it.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the fact that the study population consisted of employees of a single university, who were ultimately self-selected, and the difference found in the response rates by type of occupation, reduced the possibilities for generalising our results. We also observed that grant holders were more participative than others and were therefore over-represented, which can be explained by their reduced tendency to show neglect [13]. In general, as we did not have sociodemographic data from the total reference population, it was not possible to contrast to what extent the obtained sample was representative of it.…”
Section: Discussionmentioning
confidence: 89%
“…The factorial structure and internal consistency of the BCSQ-36 has been tested with good results [25]. This new model has also been presented in a short form as the BCSQ-12, with satisfactory results related to construct validity and predictive capacity in samples of both workers [27] and students [28]. Table 1 gives the dimensions of burnout in the classic or standard perspective provided by the “Maslach Burnout Inventory General Survey” (MBI-GS) as well as the properties of the typological model, as seen in the BCSQ-36 and BCSQ-12.…”
Section: Introductionmentioning
confidence: 99%
“…Burn-out has been described as a multi-dimensional construct comprised of exhaustion (the feeling of being unable to offer more of oneself in terms of taking on added responsibilities or applying additional effort), inefficacy (pessimistic assessments of one's own ability), and cynicism (a hostile or indifferent attitude toward work; Montero-Márin, Skapinakis, Araya, et al, 2011). Rather than viewing burnout as a personal disposition, Montero-Márin et al find that this phenomenon is more likely to occur in organizational environments which reward close compliance with procedures and either fail to recognize or punish personal initiative on the part of employees.…”
Section: Manifestations Of Limited Capabilitymentioning
confidence: 99%